Are Global Rankings Unfair to Latin American Universities? - Bernasconi, Andres (International Higher Education, 2013)
Latin American universities do poorly in global university rankings. That is, they preform below the level to be expected of the size, GDP, and level of investment in higher education of its most advanced countries. University leaders in the region react to this yearly display of the lack of international stature of their universities by blaming the instrument. They claim rankings are biased towards the "Anglo-Saxon model of the university" and that they are unfit to recognize Latin America's universities "social mission". In this article, I challenge the notion that the message conveyed by poor placements in the rankings is irrelevant to Latin American universities. I argue that the invisibility of Latin American science to the world is caused by the lack of two key resources in Latin American universities: large enough numbers of dedicated research faculty, and good institutional governance.